ANALISIS HERMENEUTIKA DAN TEKSTUALISME AL-QUR’AN (Dari Klasik hingga Kontemporer) - Zaenudin Zaenudin (al-Afkar, Journal For Islamic Studies, 2020)
The written article aims to describe the hermeneutics and Alquran textualism from classic until contemporer. Alquran in moeslim discourse, has a central position which cannot be ignored, because of the Alquran is not only a Muslim theological foundation to be religious, but also becomes law resource, moral and world view. Broadly Alquran study is consist of three main section: first, exegesis or the study of the text Alquran itself; second, the history of interpretation; and third, the role of the Alquran in life and moeslim thinking (ritual, theology, law etc). the refered hermeneutic is focus to exegesis textual as a distinctive and central element in hermeneutic. The contribute of this research is to provide thought contributions to reader to understand the hermeunetict and Alquran textualism from classic until modern.